Pengaruh Risiko Kredit Dan Risiko Likuiditas Terhadap ROA Dengan Good Corporate Governance Sebagai Variabel Moderasi - Elivia Khayidah; Mitha Otik Wiraswati; Yuli Yanti Wulansari; Dewi Agustya Ningrum (Majalah Ekonomi, 2024)
This research aims to determine the effect of credit risk and liquidity risk on ROA with Good Corporate Governance as a moderating variable. The research population consists of state-owned banks listed on the IDX, with a sample of state-owned banks for the period 2017-2021. This research uses quantitative methods, with data sources taken from the website www.idx.co.id and the official websites of each company. The analysis technique used is Moderating Regression Analysis (MRA). The research results show: (1) Credit Risk (NPL) has a negative and significant effect on ROA, (2) Liquidity Risk (LDR) has a positive but less significant effect on ROA, (3) Credit Risk (NPL) and Liquidity Risk (LDR) together have a positive and significant effect on ROA, (4) Good Corporate Governance (GCG) moderates the relationship between Credit Risk (NPL) and ROA, and (5) GCG does not moderate the relationship between Liquidity Risk (LDR) and ROA. Keywords : Good Corporate Governance; Credit Risk; Liquidity Risk; Return on Assets;